Nanoclay Reinforced Polymer Composites Nanocomposites and Bionanocomposites - Jawaid, Mohammad; Qaiss, Abou el Kacem; Bouhfid, Rachid (Engineering Materials,, 2016)
This book is part of a two-volume book series that reviews exhaustively the key recent research into nanoclay reinforced polymer composites. This is the second volume of the book series which focuses on nanoclay based nanocomposites and bionanocomposites fabrication, characterization and applications. This includes classification of nanoclay, chemical modification and processing techniques of nanocomposites. The book also provides comprehensive information about nanoclay modification and functionalization; modification of nanoclay systems, geological and mineralogical research on clays suitability; bio-nanocomposites based on nanoclays; modelling of mechanical behaviour of halloysite based composites; mechanical and thermal properties of halloysite nanocomposites; the effect of Nanoclays on gas barrier properties of polymers and modified nanocomposites. The book is a valuable reference guide for academics and industrial practitioners alike.